KALIMAT EFEKTIF DALAM TEKS EKSPLANASI SISWA KELAS XI SMA NEGERI 5 SIJUNJUNG - Dewi Marhamah Syadli; Dewi Anggraini (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
The purpose of this study was to describe the effectiveness of sentences in explanatory texts for class XI students of SMA Negeri 5 Sijunjung in terms of structural clarity, logical meaning, frugality of words, standardization of words, and spelling accuracy. This type of research is qualitative with descriptive method. The data in this study were sentences in the explanatory text of class XI students of SMA Negeri 5 Sijunjung, with a data source of 26 explanatory texts written by students of class XI SMA Negeri 5 Sijunjung. The data collection technique in this study is fishing technique. The results showed that of the 250 sentences used, only 79 sentences could be categorized as effective, while 171 sentences could not be categorized as effective. First, there are 271 ineffectiveness in terms of structural clarity. Second, the ineffectiveness in terms of logical meaning, there are 80 sentences. Third, the ineffectiveness of sentences in terms of word-saving, namely as many as 141 sentences. Fourth, the ineffectiveness of sentences in terms of word standardity, namely as many as 96 sentences. Fifth, sentence ineffectiveness in terms of spelling accuracy was found in 152 sentences.